Flood Modeling Using Hec-Ras Software Due to The Overflow of the Bengawan Solo River in Bojonegoro Regency - Aulady, Mohamad Ferdaus Noor; Kartika Sari, Nur (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
The Bengawan Solo River covers an area of approximately 16,100 km² and has a length of about 660 km. Increasing and irregular rainfall patterns have led to rising water levels in the Bengawan Solo River. Therefore, by utilizing technological advancements, floodplain modeling techniques can be applied using the HEC-RAS software as a flood disaster mitigation effort. The research method used involves calculating the flood discharge using the Synthetic Unit Hydrograph (HSS) Nakayasu method, followed by hydraulic analysis with the HEC-RAS software. The resulting flood discharge for the Q100 year return period is 11,570.98 m³/s. Based on the Q100 discharge value, the existing river cross-section is unable to accommodate the flow. From this analysis, the selected mitigation method is a structural approach in the form of river normalization.